The role of ecological specialization in shaping patterns of insular communities - Sfenthourakis, Spyros (2021)
AIM: Research on the response of species richness to area and environmental heterogeneity so far has not addressed possible effects of species’ differences in ecological specialization. Herein we provide a new metric, ‘ecorichness’, in an attempt to fill this gap. LOCATION: Aegean islands (Greece). TAXON: Terrestrial isopods. METHODS: ‘Ecorichness’ estimates an island's biodiversity by integrating species richness and the specialists-generalists spectrum. We calculated ‘ecorichness’ for terrestrial isopods from 43 Aegean islands based on the habitats they exploit. ‘Ecorichness’ then was regressed on area, habitat diversity and the K-parameter of the Choros model using linear and quadratic models, compared based on AICc. A reduced data set, without halophilous species and coastal habitats, as well as an alternative description of habitat diversity, also was explored. The small island effect (SIE) thresholds identified using both a path analysis approach and piecewise continuous linear models were compared to the area of maximum ‘ecorichness’. RESULTS: ‘Ecorichness’ response to area and habitat heterogeneity was best fitted by quadratic models with peaks located at an area similar to the SIE threshold identified by path analysis. Different measures of habitat diversity produced similar patterns. Exclusion of coastal species and habitats shows that the response of ‘ecorichness’ to area is mostly shaped by the increasing contribution of specialists in the assemblages of larger islands. MAIN CONCLUSIONS: ‘Ecorichness’ facilitates exploration of the role of ecological specialization in shaping community patterns. It can be applied to different community data sets, whenever habitat range exploitation can be quantified. Results from the case study accord with previous suggestions that the relative contribution of generalists and specialists differs between small and large island communities.